A review on research, application, processing, and recycling of PPS based materials - Montagna, Larissa Stieven; Kondo, Marcel Yuzo [UNESP]; Callisaya, Emanuele Schneider [UNESP]; Mello, Celson [UNESP]; de Souza, Bárbara Righetti; Lemes, Ana Paula; Botelho, Edson Cocchieri [UNESP]; Costa, Michelle Leali [UNESP]; de Sampaio Alves, Manoel Cléber [UNESP]; Ribeiro, Marcos Valério [UNESP]; Rezende, Mirabel Cerqueira (FapUNIFESP (SciELO), 2022)
Among the engineering thermoplastics, poly(phenylene sulfide) (PPS) stands out for its excellent properties and mainly for processing at lower temperatures. The requirements requested by industries can be made by improving mechanical strength, weight reduction, and durable components by reinforcing the PPS matrix with fiberglass (FG) and carbon fiber (CF). This review intends to present the most current research related to the physical, mechanical, and thermal properties of PPS and the PPS/FG and PPS/CF composites most currently used by the aerospace, automotive, and energy industries. In addition to presenting the feasibility of mechanical and thermal recycling processes for PPS-based waste to reinsert a high market value thermoplastic into the industrial production cycle, thus contributing to the minimization of waste destined for landfills and incinerated or even improperly disposed of in the environment.
Keywords: applications; carbon fiber; composites; fiberglass; poly(phenylene sulfide)